Subject Ellipsis in Subordinate Constructions of Acehnese Language - Iqbal, Muhammad; Mulyadi, Mulyadi; Basaria, Ida; Dardanila, Dardanila (Jurusan Sejarah, Seni, dan Arkeologi, FKIP, Universitas Jambi, 2024)
This study aims to explain the rules of subject ellipsis in subordinate constructions of the Acehnese language. The research employs a qualitative method using note-taking and document analysis techniques. The data for this study consists of written texts (complex/subordinate sentences) obtained from various sources, such as Acehnese language books and Acehnese grammar books. Additionally, data from artificial sources were also included. The results show that there are rules for subject ellipsis in subordinate constructions. The rules are as follows: First, the presence of shared understanding (mafhum). In a subordinate construction, there are two types of constituents: those that are explicitly mentioned and those that are understood. The explicitly mentioned constituent is one that is clearly stated, while the understood constituent is one that is inferred from the context of the construction. This means that the understood constituent is omitted because it is already comprehended from the previous constituent. Generally, the understood constituent appears after the explicitly mentioned constituent. Second, both constituents function as subjects. This rule explains that one of two constituents with the same reference can be omitted if both serve as subjects in the clause. Third, there is a difference in syntactic functions. This means that subject ellipsis in subordinate clauses can still occur as long as the controlling constituent does not share the same function as other constituents in the main clause (the controlled constituent functions as the subject, while the controlling constituent can function as the subject, object, complement, or adverbial).